Building Customer Loyalty of TikTok Shop Gen Z Medan City Mediation Analysis of Product Quality Satisfaction - Ismail; Salisa Amini; Nurhudawi; Arifa Pratami; Irma Suryani Lubis; Muslim Marpaung (LP2M IAIN Palopo, 2026)
Purpose: This study aims to analyze the influence of product quality on the loyalty of TikTok Shop customers generation Z in Medan City, with customer satisfaction as a mediating variable. Methods: A quantitative approach was used with the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique. The sample consisted of 75 respondents who had shopped at least three times through TikTok Shop. Result: Product quality has a significant effect on customer satisfaction (β = 0.757; p < 0.001). Product quality also has a direct and strong effect on customer loyalty (β = 0.837; p < 0.001). Customer satisfaction has a positive effect on loyalty (β = 0.182; p < 0.001) and acts as a partial mediator in the relationship between product quality and loyalty (β = 0.138; p < 0.001). Implications: These findings suggest that in order to build Gen Z customer loyalty, TikTok Shop business actors need to maintain product quality while creating a satisfying shopping experience. Theoretically, this research contributes to the testing of mediation in loyalty models, and practically, supports visual content-based marketing strategies in the digital age.